Virtual Reality applications in Dentistry - A world to be unveiled - Aluckal, Eby; Renjith, Gopika; Paulose, Anoopa (Journal of Orofacial Research, 2022)
Virtual Reality is a collection of technological devices which creates a simulated environment of real world based on graphics, which is a 3D world in which people interact virtually with others, connect with them and are subjected to different procedures and so on. It plays a vital role in pain reduction and thereby the anxiety of patients by distracting patients from the pain processing signals. In medical professionals they provide a trial and practice opportunity before the actual procedure is done in patients. With wide range of treatment modalities and better hope for treatment, this innovative technology augments traditional training methodologies and thereby enhances patient compliance by enabling a personalized service to individual patients.